Determinants of concurrent use of Biomedicine and Korean Medicine on the hypertension patients: A cross-sectional study - Jang Won Lee; Min Kyung Hyun; Ji Hyun Lee (Integrative Medicine Research)
Background: This study assessed the utilization of biomedicine and Korean Medicine (KM) among hypertension patients. Methods: The study was a cross-sectional analysis conducted using the Korean National Health and Nutrition Examination Survey (KNHANES), which is a nationwide survey conducted every year for a representative Korean population. The use of outpatient healthcare services for hypertension patients was analyzed, and the usage determinants adjusted by the demographic and health status variables were identified. A chi-square test and logistic regression analysis were used for statistical analysis using R (version 3.6.0). Results: Among 3320 hypertension patients, 208 patients (6.27%, Weighted%: 5.99%) used the biomedicine and KM concurrently. Multivariable regression analyses revealed hypertension patients who were obese (OR: 1.417, CI: 1.007–1.995) and had an experience of sickness (OR: 2.323, CI: 1.561–3.457) to be more likely to use biomedicine and KM concurrently. Conclusion: The utilization rate and determinants of the concurrent use of biomedicine and KM were identified in patients with hypertension. Although the overall usage rate was not high, the health care patterns of healthcare consumers need to be understood. Therefore, further studies on its effectiveness and safety are recommended.